Evolution of Parathyroid Hormone Receptor Family and Their Ligands in Vertebrate - On, Jason S. W.; Chow, Billy K. C.; Lee, Leo T. O. (Frontiers in Endocrinology, 2015)
The presence of the parathyroid hormones in vertebrates, including PTH, PTH-related peptide (PTHrP), and tuberoinfundibular peptide of 39 residues (TIP39), has been proposed to be the result of two rounds of whole genome duplication in the beginning of vertebrate diversification. Bioinformatics analyses, in particular chromosomal synteny study and the characterization of the PTH ligands and their receptors from various vertebrate species, provide evidence that strongly supports this hypothesis. In this mini-review, we summarize recent advances in studies regarding the molecular evolution and physiology of the PTH ligands and their receptors, with particular focus on non-mammalian vertebrates. In summary, the PTH family of peptides probably predates early vertebrate evolution, indicating a more ancient existence as well as a function of these peptides in invertebrates.